Mild pyrolytic treatment of Gmelina arborea for optimum energetic yields. Issue 1 (1st January 2019) - Adeleke, A.A.; Odusote, J. K.; Lasode, O. A.; Ikubanni, P. P.; Malathi, M.; Paswan, D.
Abstract: One of the most promising routes to produce solid biofuel from biomass is mild pyrolytic treatment (torrefaction). In the present study, mild pyrolytic treatment of Gmelina arborea was carried out to obtain optimum energetic yields (mass yield, higher heating value and energy yield). The biomass of 0.5–6 mm particle sizes were torrefied at two different temperatures, 240 and 300°C for residence time of 30 and 60 min. Full-factorial experimental method was used for the optimization of torrefaction conditions in order to produce solid fuel with high energetic yields. The analyses revealed that torrefied biomass was better in terms of heating value, proximate contents and fuel ratio. The results also showed that temperature has the largest effect on the energetic yields compared to residence time and particle size. The optimum torrefaction conditions that produced the highest energetic yields were temperature of 260°C, residence time of 60 min and particle size of 2 mm as predicted using the factorial linear models. The optimum conditions were experimentally validated and the energetic yields obtained were acutely close to those predicted using factorial linear models developed in this study. Hence, mild pyrolytic treatment at a temperature of 260° C, residence time of 60 min and particle size of 2 mm is useful to produce solid biofuel with maximum energetic yields.